Crystal face dependent intrinsic wettability of metal oxide surfaces. Issue 1 (18th July 2020) - Zhu, Zhongpeng; Yu, Zhenwei; Yun, Frank F; Pan, Deng; Tian, Ye; Jiang, Lei; Wang, Xiaolin
Abstract: Knowledge of intrinsic wettability at solid/liquid interfaces at the molecular level perspective is significant in understanding crucial progress in some fields, such as electrochemistry, molecular biology and earth science. It is generally believed that surface wettability is determined by the surface chemical component and surface topography. However, when taking molecular structures and interactions into consideration, many intriguing phenomena would enrich or even redress our understanding of surface wettability. From the perspective of interfacial water molecule structures, here, we discovered that the intrinsic wettability of crystal metal oxide is not only dependent on the chemical components but also critically dependent on the crystal faces. For example, the $( {1\bar{1}02} )$ crystal face of α-Al2 O3 is intrinsically hydrophobic with a water contact angle near 90°, while another three crystal faces are intrinsically hydrophilic with water contact angles <65°. Based on surface energy analysis, it is found that the total surface energy, polar component and Lewis base portion of the hydrophobic crystal face are all smaller than the other three hydrophilic crystal faces indicating that they have different surface states. DFT simulation further revealed that the adsorbed interfacial water molecules on each crystal face hold various orientations. Herein, the third crucial factor for surface wettability from the perspective of the molecular level is presented, that is the orientations of adsorbed interfacial water molecules apart from the macro-level chemical component and surface topography. This study may serve as a source of inspiration for improving wetting theoretical models and designing controllable wettability at the molecular/atomic level. Abstract : The study of crystal face dependent wettability has led to the discovery of a hydrophobic crystal surface of α-Al2 O3 single crystals.